Preparation method of polymer microspheres suitable for cable sheath material
Through the use of Pickering emulsion polymerization method and the use of modified nanosilicon dioxide, polymer microspheres with core-shell structures were prepared, which solved the problem of reduced performance of acrylic resin under thermal aging, and significantly improved the heat resistance and water resistance of the cable. and oxidation resistance, achieving lightweight and stable performance of cables.
Patent Information
- Application Number
- CN202411508791.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The acrylic resin of existing cable sheath material has poor heat resistance and water resistance under long-term water erosion and thermal aging, resulting in reduced performance and unable to meet the higher microsphere technology needs.
The polymer microspheres with core-shell structures were prepared by Pickering emulsion polymerization. The heat resistance, oxidation resistance and waterproof properties of the microspheres were enhanced by modifying nanosilica, and the chemistry of modified nanosilica and acrylic matrix was used. Crosslinking and surface hydrophobic modifications form stable polymer hollow microsphere structures.
It significantly enhances the heat resistance, oxidation resistance, waterproofness and corrosion resistance of the cable, makes the cable lighter, and improves the performance stability of the microspheres, which has important application value.
Smart Images

Figure BDA0005104831760000031 
Figure BDA0005104831760000032 
Figure BDA0005104831760000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of microspheres, and in particular relates to a method for preparing polymer microspheres suitable for cable sheath materials. Background Art
[0002] With the rapid development of the economy, the use and density of cables are increasing. Power cables are as indispensable to modern life as the arteries of the human body. At present, power cables for power transmission are laid underground or on special cable trays. In order to prevent the cables from being damaged by external mechanical forces, high-performance plastic or rubber is used as the outer sheath in the cable structure design. This material is relatively expensive. In addition, the main materials of the cable are metal conductors and sheaths. The conductor itself has a large weight. In addition, metal belts are set around the conductor. Some cables also have steel wire reinforcement cores. The weight of the cable also increases, which makes it difficult to lay the cable. For example, some overhead cables have higher requirements for ground support settings, which increases the difficulty of construction.
[0003] Expanded microspheres are a special type of thermoplastic hollow polymer microspheres, which consist of a thermoplastic polymer shell and sealed alkane gas. When heated, these microspheres will expand significantly due to the increase in gas pressure in the shell and the softening of the thermoplastic shell. When cooled, the shell hardens again and the volume is fixed. Using expanded microspheres as one of the raw materials for preparing cable sheath materials, the specific gravity of the base material can be reduced through the expansion effect of the microspheres, which not only saves the preparation cost of the cable, but also reduces the weight of the cable, making the cable lighter.
[0004] Commonly used high molecular polymer matrices for polymer microspheres include acrylic resin, phenolic resin, styrene and vinyl chloride copolymers, etc. Among them, acrylic resin is inexpensive, has little environmental pollution and good performance, and is an ideal raw material for high molecular polymer microspheres. However, acrylic resin has poor heat resistance and waterproof properties. Under long-term water erosion and thermal aging, the performance of acrylic resin will be greatly reduced. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of microsphere technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing polymer microspheres suitable for cable sheath materials.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing polymer microspheres suitable for cable sheath materials comprises the following steps:
[0008] Acrylic acid, methyl methacrylate, styrene and an emulsifier are mixed and added to deionized water and stirred evenly. Modified nano-silica is then added, and the mixture is placed in an ice bath for ultrasonic treatment for 15 minutes to generate an emulsion. An initiator is added to the emulsion, and nitrogen is introduced as a protective gas. The mixture is mechanically stirred in a water bath at 60-80° C. for 24 hours, and the product is centrifuged, washed with pure water and ethanol, and dried to obtain polymer microspheres.
[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 18-25 parts of acrylic acid, 16-24 parts of methyl methacrylate, 12-18 parts of styrene, 2-6 parts of emulsifier, 120-150 parts of deionized water, 8-16 parts of modified nano-silicon dioxide, and 0.2-0.4 parts of initiator.
[0010] Furthermore, the initiator is one of potassium persulfate and azobisisobutyronitrile.
[0011] Furthermore, the emulsifier is one of alkylphenol polyoxyethylene ether and sodium lauryl sulfate.
[0012] Pickering emulsion polymerization is used to prepare polymer microspheres with a core-shell structure. Nano-silicon dioxide particles are distributed on the surface of the acrylic core in a single-layer hexagonal close-packed manner. Pickering emulsion is also called solid particle stabilized emulsion. The prepared polymer microspheres have good stability. After heat treatment, the core-shell polymer microspheres will expand internally to form a polymer hollow microsphere structure. Using them in cables can reduce the material consumption of the cables and make the cables lighter. In addition, the polymer matrix of the prepared polymer microspheres is acrylic resin, which has good performance.
[0013] Furthermore, the modified nano-silicon dioxide is prepared by the following steps:
[0014] S1. Mix nano-silica with ethanol aqueous solution, add to a magnetic stirring device, add a magnet, start stirring, disperse for 30 minutes, so that the nano-silica is evenly dispersed in the ethanol aqueous solution, evacuate the device, pass N2 gas, then add γ-aminopropyltriethoxysilane (silane coupling agent KH-550), start oil bath heating, set to 50°C, turn on condensation water, set to 80°C for 4h, filter, wash with ethanol, and then dry in a vacuum drying oven for 2h to obtain pre-modified nano-silica; the ratio of nano-silica, ethanol aqueous solution, and γ-aminopropyltriethoxysilane is 2.0g:100mL:5.5g;
[0015] There are many -OH groups on the surface of nano-silica, which can be introduced into -NH2 active groups by reacting with KH-550 to obtain pre-modified nano-silica. The specific reaction process is as follows:
[0016]
[0017] S2. Add 1,3-acetone dicarboxylic acid, diethylamino sulfur trifluoride (DAST) and dichloromethane into a flask, stir and mix evenly at room temperature, react for 45 minutes, filter, take the filter cake, wash with anhydrous ethanol 3-4 times, and vacuum dry to obtain intermediate 1; the ratio of 1,3-acetone dicarboxylic acid, diethylamino sulfur trifluoride and dichloromethane is 14.6 g:7.4 g:50 mL;
[0018] Under the action of the fluorination reagent, the carbonyl group on 1,3-acetone dicarboxylic acid is converted into a difluorinated compound. The fluorination reagent is selective and the carboxyl group is not affected, thereby obtaining intermediate 1. The specific reaction process is as follows:
[0019]
[0020] S3. In a three-necked flask equipped with a stirring device, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine (condensing agent) and toluene were mixed, the temperature was raised to 30°C, and the mixture was stirred until the solid was completely dissolved. Ethyleneguanamine was added, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 5 hours. After the reaction was completed, the mixture was naturally cooled and distilled under reduced pressure to obtain intermediate 2; the ratio of the amount of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine, toluene and vinylguanamine was 23.4 g:15 mL:100 mL:15.1 g;
[0021] Under the action of the condensing agent, the amino group on the vinylguanamine condenses with the aldehyde group on the 3,5-di-tert-butyl-4-hydroxybenzaldehyde to form an imine group (C=N Schiff base structure), and by controlling the molar ratio of the two to be close to 1:1 and the vinylguanamine to be slightly excessive, only one amino group on the vinylguanamine participates in the reaction to obtain intermediate 2; the specific reaction process is as follows:
[0022]
[0023] S4. Add intermediate 1, intermediate 2, dicyclohexylcarbodiimide (DCC, dehydrating agent) and N,N-dimethylformamide (DMF) to a three-necked flask equipped with a stirring device, stir and mix well, place in a water bath at 55°C, heat in a water bath for 7 hours, and when the reaction is finished, filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two is 3:2), remove the eluent by rotary evaporation to obtain a modifier; the ratio of intermediate 1, intermediate 2, dicyclohexylcarbodiimide and toluene is 17.2g:35.3g:20.6g:150mL;
[0024] Under the action of DCC, intermediate 1 and intermediate 2 undergo amidation reaction. By controlling the molar ratio of the two to be close to 1:1 and the intermediate 1 to be slightly excessive, only one carboxyl group on intermediate 1 participates in the reaction to obtain a modifier. The specific reaction process is as follows:
[0025]
[0026] S5. Add N,N-dimethylformamide, dicyclohexylcarbodiimide and pre-modified nano-silica into a flask, disperse evenly by ultrasonication for 35 minutes, add a modifier, slowly heat up to 65°C, start magnetic stirring (speed 1000r / min), stop heating after stirring for 5 hours, filter after the temperature in the reaction bottle drops to room temperature, wash with anhydrous ethanol 3-4 times, freeze-dry, grind, and obtain modified nano-silica; the ratio of N,N-dimethylformamide, dicyclohexylcarbodiimide, pre-modified nano-silica, and modifier is: 100mL: 15.5g: 5g: 13.4g;
[0027] The carboxyl group on the modifier reacts with the amino group on the pre-modified nano-silica to obtain modified nano-silica; the structure of the modified nano-silica is shown below:
[0028]
[0029] The prepared modified nano-silica is grafted with a modifier through chemical bonding, that is, an organic layer is formed on its surface, which can greatly improve the surface hydrophobicity of the nano-silica and improve the compatibility of the nano-silica with the matrix, which not only makes the Pickering emulsion more stable, but also makes the performance of the nano-silica fully exerted, and greatly enhances the heat resistance of the matrix; in addition, one end of the modified nano-silica contains a carbon-carbon double bond, which can produce chemical cross-linking with the acrylic matrix, and improve the mechanical strength of the matrix to a certain extent; not only that, the grafted modifier also contains a CF bond, a benzene ring and a hindered phenol structure, among which the CF bond has a small polarity, At the same time, the CF bond has a very strong bond energy. The higher the chemical bond energy, the better the stability, which further improves the heat resistance of the matrix and also gives the matrix excellent waterproof performance. Not only that, the CF bond will well coat the CC main chain, shield it, reduce the surface energy of the matrix, and greatly enhance the matrix's acid and alkali corrosion resistance. The introduced benzene ring belongs to the hydrophobic matrix, which further enhances the waterproof performance of the matrix. Finally, the hindered phenol structure has excellent antioxidant properties, which can not only improve the antioxidant performance of the matrix, but also act as an antioxidant in the production process of cables, avoiding the addition of additional antioxidants and affecting the homogeneity of the cable.
[0030] It should be added that the nano-silica grafted modifier can prevent the migration and seepage of small molecules of the modifier and improve the durability of the performance.
[0031] Beneficial effects of the present invention:
[0032] 1. The present invention utilizes Pickering emulsion polymerization to prepare polymer microspheres. The prepared polymer microspheres have good stability, a core-shell structure, and expand after heat treatment. They can be used to reduce the material used in cables and make the cables lighter.
[0033] 2. By modifying nano-silica, compared with ordinary nano-silica, it has better compatibility with acrylic matrix, and can also improve the heat resistance, oxidation resistance, water resistance and corrosion resistance of microspheres, and the performance is long-term and stable;
[0034] Therefore, the microspheres prepared by the present invention can be used in cables to make the cables lighter, and can also significantly enhance the heat resistance, oxidation resistance, water resistance and corrosion resistance of the cables, and the performance is long-lasting and stable, which has important application value in the field of microsphere technology. DETAILED DESCRIPTION
[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] Preparation of modified nano-silica:
[0038] S1. Mix 2.0 g of nano-silica with 100 mL of ethanol aqueous solution, add to a magnetic stirring device, add a magnet, start stirring, disperse for 30 min, make the nano-silica evenly dispersed in the ethanol aqueous solution, evacuate the device, pass N2 gas, add 5.5 g of silane coupling agent KH-550, start oil bath heating, set to 50 ° C, turn on condensation water, set to 80 ° C for 4 h, filter, wash with ethanol, and then dry in a vacuum drying oven for 2 h to obtain pre-modified nano-silica;
[0039] S2, add 14.6g 1,3-acetone dicarboxylic acid, 7.4g diethylamino sulfur trifluoride and 50mL dichloromethane into a flask, stir and mix evenly at room temperature, react for 45min, filter, take the filter cake, wash it with anhydrous ethanol for 3 times, and dry it in vacuum to obtain intermediate 1;
[0040] S3, in a three-necked flask equipped with a stirring device, 23.4g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 15mL of piperidine and 100mL of toluene were mixed, the temperature was raised to 30°C, and the mixture was stirred until the solid was completely dissolved, 15.1g of vinylguanamine was added, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 5h. After the reaction was completed, the mixture was naturally cooled and distilled under reduced pressure to obtain intermediate 2;
[0041] S4. Add 17.2 g of intermediate 1, 35.3 g of intermediate 2, 20.6 g of dicyclohexylcarbodiimide and 150 mL of N,N-dimethylformamide to a three-necked flask equipped with a stirring device, stir and mix well, place in a 55° C. water bath, heat in a water bath for 7 h, and complete the reaction. Filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 3:2), and remove the eluent by rotary evaporation to obtain a modifier;
[0042] S5. Add 100 mL of N,N-dimethylformamide, 15.5 g of dicyclohexylcarbodiimide and 5 g of pre-modified nano-silica into a flask, disperse evenly by ultrasonication for 35 min, add 13.4 g of modifier, slowly heat up to 65 °C, start magnetic stirring (speed 1000 r / min), stop heating after stirring for 5 h, wait for the temperature in the reaction bottle to drop to room temperature, filter, wash with anhydrous ethanol 3 times, freeze-dry, and grind to obtain modified nano-silica.
[0043] Example 2
[0044] Preparation of modified nano-silica:
[0045] S1. Mix 4.0 g of nano-silica with 200 mL of ethanol aqueous solution, add to a magnetic stirring device, add a magnet, start stirring, disperse for 30 min, make the nano-silica evenly dispersed in the ethanol aqueous solution, evacuate the device, pass N2 gas, add 11.0 g of silane coupling agent KH-550, start oil bath heating, set to 50 ° C, turn on condensation water, set to 80 ° C for 4 h, filter, wash with ethanol, and then dry in a vacuum drying oven for 2 h to obtain pre-modified nano-silica;
[0046] S2, add 29.2g 1,3-acetone dicarboxylic acid, 14.8g diethylamino sulfur trifluoride and 100mL dichloromethane into a flask, stir and mix evenly at room temperature, react for 45min, filter, take the filter cake, wash it with anhydrous ethanol 4 times, and dry it in vacuum to obtain intermediate 1;
[0047] S3, in a three-necked flask equipped with a stirring device, 46.8g of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, 30mL of piperidine and 200mL of toluene were mixed, the temperature was raised to 30°C, and the mixture was stirred until the solid was completely dissolved, 30.2g of vinylguanamine was added, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 5h. After the reaction was completed, the mixture was naturally cooled and distilled under reduced pressure to obtain intermediate 2;
[0048] S4. Add 34.4 g of intermediate 1, 70.6 g of intermediate 2, 41.2 g of dicyclohexylcarbodiimide and 300 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirring device, stir and mix evenly, place in a water bath at 55° C., heat in a water bath for 7 h, and terminate the reaction. Filter, remove the solvent by vacuum distillation, and purify by column chromatography (the eluent is a mixed solvent of benzene / ethyl acetate, the volume ratio of the two is 3:2), and remove the eluent by rotary evaporation to obtain a modifier;
[0049] S5. Add 200 mL of N,N-dimethylformamide, 31.0 g of dicyclohexylcarbodiimide and 10 g of pre-modified nano-silica into a flask, disperse evenly by ultrasonication for 35 min, add 26.8 g of modifier, slowly heat up to 65 °C, start magnetic stirring (speed 1000 r / min), stop heating after stirring for 5 h, wait for the temperature in the reaction bottle to drop to room temperature, filter, wash with anhydrous ethanol 4 times, freeze-dry, and grind to obtain modified nano-silica.
[0050] Example 3
[0051] 18 g of acrylic acid, 16 g of methyl methacrylate, 12 g of styrene and 2 g of alkylphenol polyoxyethylene ether were mixed and added into 120 g of deionized water and stirred evenly, and then 8 g of the modified nano-silica prepared in Example 1 was added, and after mechanical stirring for 15 min, the mixture was placed in an ice bath and ultrasonicated for 15 min to generate an emulsion; 0.2 g of potassium persulfate was added to the emulsion, and nitrogen was introduced as a protective gas. After mechanical stirring in a water bath at 60° C. for 24 h, the product was centrifuged, washed with pure water and ethanol, and dried to obtain polymer microspheres.
[0052] Example 4
[0053] 22g of acrylic acid, 20g of methyl methacrylate, 15g of styrene and 4g of alkylphenol polyoxyethylene ether were mixed and added into 135g of deionized water and stirred evenly, and then 12g of the modified nano-silica prepared in Example 2 was added, and after mechanical stirring for 25min, the mixture was placed in an ice bath and ultrasonicated for 15min to generate an emulsion; 0.3g of azobisisobutyronitrile was added to the emulsion, and nitrogen was introduced as a protective gas. After mechanical stirring in a water bath at 70°C for 24h, the product was centrifuged, washed with pure water and ethanol, and dried to obtain polymer microspheres.
[0054] Example 5
[0055] 25 g of acrylic acid, 24 g of methyl methacrylate, 18 g of styrene and 6 g of sodium dodecyl sulfate were mixed and added to 150 g of deionized water and stirred evenly, and then 16 g of the modified nano-silica prepared in Example 2 was added, and after mechanical stirring for 30 min, it was placed in an ice bath and ultrasonicated for 15 min to generate an emulsion; 0.4 g of azobisisobutyronitrile was added to the emulsion, and nitrogen was introduced as a protective gas. After mechanical stirring in a water bath at 80° C. for 24 h, the product was centrifuged, washed with pure water and ethanol, and dried to obtain polymer microspheres.
[0056] Comparative Example 1
[0057] Ordinary nano-silica of the same mass was used to replace the modified nano-silica in Example 5, and the remaining steps were the same as in Example 5 to prepare polymer microspheres.
[0058] Comparative Example 2
[0059] Commercially available acrylate microspheres were used.
[0060] The polymer microspheres prepared in Example 3 were mixed with a small amount of water, and a drop was taken on a glass slide of a metallographic microscope. The particle size of the obtained microspheres was measured using a metallographic microscope, and the average particle size was found to be in the range of 5.5-12.3 μm. The polymer microspheres prepared in Example 3 were heat-treated, and after the treatment, the same method was used to obtain an average particle size in the range of 32.2-42.5 μm.
[0061] The microspheres of Examples 3-5 and Comparative Examples 1-2 were respectively used as one of the raw materials for preparing cable materials to prepare cable materials. The preparation process was as follows:
[0062] 80g of polyvinyl chloride resin, 12g of polyethylene, 2g of trimethylolpropane triacrylate (cross-linking agent), 10g of expanded microspheres and 4g of paraffin (lubricant) are added to a high-speed mixer in sequence for mixing. After mixing evenly, the mixture is transferred to a twin-screw plasticator for plasticizing. After plasticizing evenly, the mixture is water-cooled and drawn into strips, and then pelletized. The mixture is then dried in a centrifugal dryer to obtain a cable material.
[0063] The cable materials prepared from the raw materials of Examples 3-5 and Comparative Examples 1-2 were made into corresponding shapes according to different test standards and the following performance tests were performed:
[0064] The national standard GB / T 19466.6-2009 "Plastic Differential Scanning Calorimetry" was used to measure the induction time of the sample before and after hot air oxidation at 150°C for 48 hours.
[0065] The national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics" was used to measure the tensile properties of the samples before and after alkali treatment, acid treatment, and water treatment, and the tensile strength retention rate was calculated; tensile strength retention rate = tensile strength after test / tensile strength before test × 100%;
[0066] Alkali treatment: sodium hydroxide solution with a pH value of 13 in a 50°C water bath for 4 hours;
[0067] Acid treatment: hydrochloric acid solution with a pH value of 2 in a 50°C water bath for 4 hours;
[0068] Water treatment: immerse the sample in water at 50℃ for 12h;
[0069] The measured results are shown in the following table:
[0070]
[0071] It can be seen from the above table that the polymer microspheres prepared in the embodiments of the present invention can be used to prepare cable sheath materials, which can significantly enhance the heat resistance, oxidation resistance, waterproofness and corrosion resistance of the cable, and have important application value in the field of microsphere technology.
[0072] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0073] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing polymer microspheres suitable for cable sheath materials, characterized in that: The following steps are involved: Acrylic acid, methyl methacrylate, styrene and emulsifier are mixed and added into deionized water and stirred evenly, and then modified nano-silica is added, and an emulsion is generated after stirring and ultrasonication for 15 minutes; an initiator is added, and nitrogen is introduced, and the reaction is stirred at 60-80°C for 24 hours, centrifuged, washed with pure water and ethanol, and dried to obtain polymer microspheres.
2. The method for preparing polymer microspheres suitable for cable sheath materials according to claim 1, characterized in that: The modified nano silicon dioxide is prepared by the following steps: S1. Mix nano-silica with ethanol aqueous solution, start stirring, disperse for 30 minutes, evacuate, introduce N2 gas, add γ-aminopropyltriethoxysilane, heat, set to 50°C, turn on condensation water, set to 80°C for 4 hours, filter, wash, and dry to obtain pre-modified nano-silica; S2, add 1,3-acetone dicarboxylic acid, diethylamino sulfur trifluoride and dichloromethane into a flask, stir and mix evenly at room temperature, react for 45 minutes, filter, take the filter cake, wash and dry to obtain intermediate 1; S3, 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine and toluene were mixed, the temperature was raised to 30°C, and after stirring, ethyleneguanamine was added, and the mixture was reacted at 60°C for 5 hours. After the reaction was completed, the mixture was naturally cooled and distilled under reduced pressure to obtain intermediate 2; S4, after mixing the intermediate 1, the intermediate 2, dicyclohexylcarbodiimide and N,N-dimethylformamide, heating at 55° C. for 7 h, the reaction is completed, filtering, vacuum distillation, column chromatography purification, rotary evaporation, to obtain a modifier; S5. Add N,N-dimethylformamide, dicyclohexylcarbodiimide and pre-modified nano-silica into a flask, disperse them evenly by ultrasonication for 35 minutes, add the modifier, stir at 65°C for 5 hours and then stop heating. After cooling to room temperature, filter, wash, dry and grind to obtain modified nano-silica.
3. The method for preparing polymer microspheres suitable for cable sheath materials according to claim 2, characterized in that: In step S1, the ratio of the amount of nano-silica, the ethanol aqueous solution, and γ-aminopropyltriethoxysilane is 2.0 g:100 mL:5.5 g.
4. The method for preparing polymer microspheres suitable for cable sheath materials according to claim 2, characterized in that: In step S2, the ratio of 1,3-acetonedicarboxylic acid, diethylaminosulfur trifluoride, and dichloromethane is 14.6 g:7.4 g:50 mL.
5. The method for preparing polymer microspheres suitable for cable sheath materials according to claim 2, characterized in that: In step S3, the ratio of the amount of 3,5-di-tert-butyl-4-hydroxybenzaldehyde, piperidine, toluene and vinylguanamine is 23.4 g:15 mL:100 mL:15.1 g.
6. The method for preparing polymer microspheres suitable for cable sheath materials according to claim 2, characterized in that: In step S4, the ratio of the amount of intermediate 1, intermediate 2, dicyclohexylcarbodiimide and toluene is 17.2 g: 35.3 g: 20.6 g: 150 mL.
7. The method for preparing polymer microspheres suitable for cable sheath materials according to claim 2, characterized in that: In step S5, the ratio of the amount of N,N-dimethylformamide, dicyclohexylcarbodiimide, pre-modified nano-silica, and modifier is: 100 mL: 15.5 g: 5 g: 13.4 g.
8. The method for preparing polymer microspheres suitable for cable sheath materials according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 18-25 parts of acrylic acid, 16-24 parts of methyl methacrylate, 12-18 parts of styrene, 2-6 parts of emulsifier, 120-150 parts of deionized water, 8-16 parts of modified nano-silicon dioxide, and 0.2-0.4 parts of initiator.
Citation Information
Cited By
Low-temperature-resistant modified PPR (polypropylene random copolymer) and preparation process thereof
CN119978691A
Lightweight anti-aging cable sheath material based on expanded microspheres and preparation method of lightweight anti-aging cable sheath material
CN120082146A
A lightweight and aging-resistant cable sheath material based on expandable microspheres and its preparation method
CN120082146B